COMBINING PROSTATE HEALTH INDEX AND mpMRI DATA (MRI SPECTROSCOPY) TO MANAGE PI-RADS LESIONS AND REDUCE EXCESSIVE BIOPSY, A SINGLE CENTER STUDY - Krstev, Toni; Stojanoski, Ivica; Ilievski, Lazar; Tufekchioski, Nerhim; Prgova-Veljanova, Biljana; Kostova, Masha; Stojcheva-Taneva, Olivera; Trojacanec, Jasmina; Milenkovski, Stefan (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
To evaluate the values ​​of PHI and PI-RADS findings in the early detection and prediction of prostate cancer, as well as their application in clinical trials, especially when values of PSA are in the „ grey zone„ with negative DRE. 100 patients, men aged 50 years or older with prostate specific antigen 4 to 10 ng/ml („gray zone„) and normal digital rectal examination with suspected prostate cancer were examined, who had undergone biopsy and were divided in two groups. A group with no evidence of PCa (non PCa) and the group with PCa. The performance of PHI and mpMRI PI-RADS score was compared to predict biopsy results and, specifically, the presence of clinically significant prostate cancer (csPCa) using multiple criteria. Among 100 subjects, 21 (21.0%) were diagnosed with PC, including 13 (61.95%) with csPC (Gleason≥7). By the threshold of PHI≥36, the sensitivity, specificity, PPV, and NPV to predict PCa were 100%, 68.35%, 45.65%, and 100%, respectively. The best cut-off (PHI) was 42.8% with sensitivity 85.7% and specificity 86.1%. The area under the receiver operator characteristic curve (AUC) of combining PHI and mpMRI was greater than that of PHI alone (0.993 vs. 0.954, p=0.002) and mpMRI alone (0.993 vs. 0.976, p=0.025). Comparing the performance in the identification of clinically significant prostate cancer (csPCa), we found that PHI ≥ 73.04 and PI-RADS score ≥ 4 were able to identify csPCa (Gleason score ≥ 7 (3 + 4)) both alone and added to a base model including age, PSA, fPSA-to-tPSA ratio and prostate volume. If biopsy was restricted to patients with PI-RADS 5 as well as PI-RADS 3 or 4 and PHI≥36.0, 50% of biopsy could be avoided with one csPCa patient being missed. The analyzed correlation between PHI and PI-RADS score was statistically significant (p<0.0001). According to the value of Spearman's coefficient, R=0.748, the correlation is positive, i.e. direct, and they showed that with an increase in the value of the prostatic health index, (PHI) the PI-RADS score increases, and vice versa. The combination of PHI and mpMRI had higher accuracy for detection of csPC compared with PHI or mpMRI alone. Keywords: Prostate health index, mpMRI  PI-RADS, detection of prostate cancer.